Comparison between ‘three in one femoral nerve block’ and psoas compartment block for post-operative pain relief following lower limb surgical procedures - Namasivayam, S. Ponnambala; Arivazhagan, S.; Saravanakumar, S. (International Journal of Research in Medical Sciences, 2017)
Aim of this study was to compare anterior approach (‘three in one block’) and posterior approach (psoas compartment block) of lumbar plexus block in relieving the post-operative pain in patients operated for unilateral hip, femur or knee surgery under spinal anaesthesia. 40 patients undergoing elective orthopedic procedure in hip, femur or knee were randomized into group A and group B. Surgery was done under spinal anaesthesia. At the end of the surgery, single shot lumbar plexus block was given by anterior approach (3 in 1 block) in group A and by posterior approach (psoas compartment block) in group-B patients with 30 ml of 0.25% of bupivacaine. Pain was assessed using verbal rating scale. The time for first rescue analgesic, need of additional analgesic and overall satisfaction of post-operative pain relief were noted. Both the groups were comparable in age, sex, weight, height, vital signs, duration and type of surgery. There is no significant difference in pain level between two groups. The mean time for first rescue analgesia was 9.10 (± 1.52) and 9.90 (± 1.21) hours in group A and group B respectively (p>0.05 not significant). Requirement of additional analgesic was reduced in both groups. More than 90% of patients expressed overall satisfaction of post-operative pain relief in both groups. Both approaches of lumbar plexus block by Three in one femoral nerve block (Group A) and psoas compartment block (Group B) were effective in providing post-operative analgesia after hip, femur, or knee surgery.